Decision Support System for Employee Performance Assessment Using Analytical Hierarchy Process and Simple Additive Weighting Methods - Suprapto, Yulisnio Prasakti; Haerudin, Haerudin; Danuwidodo, Agus (Journal of Information System and Informatics, 2024)
Evaluation of employee performance is carried out by company leaders at company work meetings to determine the best employees. In the process of assessing the best employees, the relevant company still does not use a digital system and does not have a clear weighting system for the criteria used. This results in inaccurate assessment results. Based on the problems found during field observations, research was carried out with the aim of developing a computerized decision support system for employee performance assessment and a system that applies weighting to each criterion. The Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) methods are the methods used in developing this decision support system. The AHP method is used to determine the weight of each criterion, while the SAW method is used to determine the ranking of the best employees. The research results are in the form of a website-based decision support system complete with criteria and weights for each criterion as well as the final results of the performance assessment of the 5 data samples used. This system has been tested using the User Acceptance Test method and obtained a score of 78.31%.